Mobile Cache Memory Optimization using Noise Reduction - Amudha Bhomini, P; Jayasudha, JS (International Journal of Computer Sciences and Engineering, 2025)
Web pages not only contains useful information, but also many features to improve readability and presentation which end up distracting the relevant content as well as occupying more precious memory space. It becomes even more problem while stored in limited mobile cache and prefetch area. While caching and prefetching or when a page is used repeatedly these unnecessary content, called noise such as banner, advertisements, copyright, background images and license information etc. occupy more space, bandwidth while it doesn’t add any value to the user of actual content. Eliminating such noises helps in overall performance improvement of mobile caching, and perfecting. If such noises are not removed, they will become nuisance in web content mining as well. There are many contents which can be identified as noise and there are many techniques to remove them. This paper identifies and removes irrelevant noises in web pages such as background images, search panel, copyright, license information, advertisement. Removing image heavy contents reduces cache memory utilisation, improves performance of content rendering considerably. Care is taken only to remove noises identified and leave the useful contents intact. A brief over view of noise removal and its benefits are discussed in this paper.